2015
DOI: 10.1097/md.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation and Prognostic Value of Positron Emission Tomography-Computed Tomography After Induction Chemotherapy With or Without Radiation in IIIA-N2 Non-small Cell Lung Cancer Patients Who Receive Curative Surgery

Abstract: We evaluate the correlation of clinical staging on positron emission tomography-computed tomography (PET-CT) and pathologic staging and the prognostic value of PET-CT after induction chemotherapy in patients with locally advanced nonsmall cell lung cancer (NSCLC).We analyzed 42 cases of clinical stage IIIA-N2 NSCLC who receive 2 to 4 cycles of preoperative chemotherapy with or without radiation followed by curative resection. The maximum standard uptake value (SUVmax) of the suspected lesion on PET-CT was reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The median follow-up time of the present study is 34 months, and it is shorter than those of other studies. 4 , 8 , 29 , 30 This may explain the excellent survival outcome regardless of the KRAS oncogene status in our study, and longer follow-up would be helpful to elucidate the value of the KRAS oncogene and its mutation more clearly. 31 …”
Section: Discussionmentioning
confidence: 69%
“…The median follow-up time of the present study is 34 months, and it is shorter than those of other studies. 4 , 8 , 29 , 30 This may explain the excellent survival outcome regardless of the KRAS oncogene status in our study, and longer follow-up would be helpful to elucidate the value of the KRAS oncogene and its mutation more clearly. 31 …”
Section: Discussionmentioning
confidence: 69%
“…A number of clinical studies have shown that alterations in metabolic activity, expressed as changes in SUV during induction therapy or at interim evaluation, are associated with tumor response. In NSCLC, a reduction of SUVmax below 2.5 after 2-4 conventional chemotherapy cycles has been considered a predictor of future response associated with a substantially higher median time to recurrence ( 28 ). Similarly, when the treatment studied is a targeted therapy, such as the EGFR tyrosine-kinase inhibitor erlotinib, a reduction in SUVmax measured by [ 18 F]-FDG-PET is also clearly associated with durable therapeutic responses in NSCLC patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, treatment response in NSCLC is still largely assessed with conventional CT. A recent study from Israel evaluating the use of FDG PET-CT to assess the resectability of patients with stage III NSCLC after neoadjuvant therapy reported a very high sensitivity and negative predictive value for detecting responding nodes, which may guide optimal patient selection for curative resection 107 . Another recent study from Korea evaluating a similar patient cohort reported significantly increased relapse-free and overall survival in patients undergoing surgery who showed CMR within mediastinal nodal disease on FDG PET-CT following neoadjuvant treatment compared to incomplete responders 108 .…”
Section: Treatment Response In Lung Carcinomamentioning
confidence: 90%